Improving Second Semester Student's Learning Outcomes in Sharia Business Course trough the Implementation of Cooperative Learning Model Think Pair Share (TPS) In the Faculty of Economics Muhammadiyah University of North Sumatera - Dr. Sri Mujiatun, S.E., M.M. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
-